The Role of Pro-Innovative HR Practices and Psychological Contract in Shaping Employee Commitment and Satisfaction: A Case from the Energy Industry - Gadomska-Lila, Katarzyna; Rogozińska-Pawełczyk, Anna (Energies (Basel), 2022)
Innovation is a very important attribute of energy companies. Its level largely depends on employees’ attitudes and behaviours, which are determined on the one hand by individual factors (e.g., psychological contract) and on the other hand by organisational factors (e.g., human resources (HR) practices). The aim of this article is to identify the relationship between pro-innovative HR practices, psychological contract and employee attitudes—commitment and job satisfaction. The research was conducted in a company which is one of the leading Polish electricity suppliers. Data were collected using a proprietary survey questionnaire. The research involved 402 HR professionals responsible for shaping and implementing pro-innovative HR practices in the company. Hypotheses were tested using the partial least squares structural equation modelling technique (PLS-SEM). The results indicate the existence of a positive relationship between pro-innovative HR practices, psychological contract and employee commitment and satisfaction. Furthermore, they indicate that organisations wishing to increase employee commitment and job satisfaction should strengthen and implement existing psychological contracts. One way to do this is to invest in pro-innovative HR practices, such as competence development, knowledge sharing or creativity-based candidate selection, as they have been shown to be good moderators of these relationships. The obtained results may be of particular importance for HR management specialists and managers responsible for shaping desired attitudes and behaviours of employees.